Intravenous thrombolysis with rt-plasminogen activator in patients with acute ischemic stroke: clinical experience from two Egyptian centers - Nabil Mohamed; Ahmed Nemr; Hussein ElGharieb; Ahmed Essmat; Elsayed Ahmed (Wolters Kluwer Medknow Publications, 2020)
Objective Stroke is one of the leading causes of disability and death worldwide. Intravenous thrombolytic therapy has been widely recommended as a standard treatment for acute ischemic stroke in most clinical practice guidelines. The authors aimed to report on the efficacy and safety of rt-plasminogen activator (PA) in the management of acute ischemic stroke in a sample of Egyptian patients. Patients and methods There were 58 patients treated with IV rt-PA within 4.5 h of stroke onset during the study period between 2014 and 2018 at the Stroke Units of Al-Azhar University Hospitals and Al-Maadi Military Hospital. Results The studied patients had an age of 62.55±9.94 years and comprised 36 men and 22 women. Treatment window was within the first 3 h of stroke onset in 24 (41.3%) patients, while it was within 3-4.5 h in 34 (58.7%) patients. Forty-six (79.3%) patients had an early improvement and the remaining 12 (20.7%) patients experienced early deterioration. Treatment complications included symptomatic intracranial hemorrhage (10.3%), asymptomatic intracranial hemorrhage (3.4%), and hematuria (3.4%). The in-hospital mortality rate was 10.3%. Comparison between patients with early improvement and those with early deterioration shows significant association between treatment within the first 3 h of stroke onset and early improvement. Conclusions The authors have been able to show that IV thrombolysis is feasible and safe in our hospitals. However, the number of stroke patients receiving rt-PA in the developing world is relatively low.